Experimental Study on Building Demolished Waste Stabilized Expansive Soil with Potassium Chloride - M. Ganesh, K; S.S.Vara Prasad, A; Jagapathi Raju, M (International Journal of Engineering and Technology, 2018)
All the civil engineering Â projects such as highways, water reservoirs, railways, buildings etc. requires large quantity of earth material. The mankind was wondering about the instability of earth materials especially expansive soil for centuries. Large areas are being covered with highly plastic and expansive soil quite often which is not suitable for such purpose. They can be hard when dry and they can be soft in moist conditions. Soils subjected to volumetric changes with seasonal moisture variation always create problem for lightly loaded structure by consolidating under load. It results in excessive settlement of superstructures usually and differential movements causing damage to foundation systems, structural elements and architectural features. Promising results were obtained by various researchers for the application of such expansive soil after stabilization with additives such as sand, silt, lime, fly ash, etc. A relatively new solid waste, Building Demolished Waste (BDW), can be used for stabilization of expansive soils for various uses in combination with potassium chloride. This study was planned to access the role of potassium chloride inclusions in improving the weak expansive soil besides stabilizing it with Building Demolished Waste in different proportions.Â Â